Factors influencing employee engagement via online teaching during Covid-19 pandemic - Hanis Munawwarah, Ahmad Murad (2021)
The recent Covid-19 pandemic has introduced unprecedented changes in the higher education institute (HEI) sector, including a full transition to online teaching and learning (OTL), and changes in working environment and arrangement of the academicians. In midst of the changes, the question of whether these changes would influence employee engagement (EE) among academic staff arises. Underpinned by Kahn’s theory of engagement, this study aimed to study the influence of Big Five personality (BFP), perceived organizational support (POS), and job satisfaction (JS) on employee engagement level of academic staff. A total of 296 academic staff from two universities in the northern region of Malaysia had participated in the online questionnaire consisted of 9-item Utrecht Work Engagement Scale (UWES-9), 28-item adapted version of Big Five Inventory-44 (BFI-44), 8-item shortened version of perceived organizational support (SPOS) survey and 7-item general satisfaction measure. The data was run through SmartPLS 3.0 and was analyzed by bootstrapping analysis utilizing the partial least square-structural equation modelling (PLS-SEM) method to test the hypotheses. The results showed that, out of the five BFP domains, only extraversion and neurotic personalities significantly influence EE level, while conscientiousness, agreeableness, and openness to experience do not significantly influences EE. The other two independent variables, POS and JS, were also found to influence EE significantly. Out of all the independent variables, in terms of their relationship with EE, only conscientiousness and openness to experience personalities were found to demonstrate different results compared to most findings in past similar studies conducted pre-pandemic. Finally, this study also discusses implication for management level and suggested some recommendations for future studies.